Countermeasure against probabilistic blinding attack in practical quantum key distribution systems - 钱泳君 李宏伟 何德勇 银振强 张春梅 陈巍 王双 韩正甫 (Chinese physics B, 2015)
In a practical quantum key distribution（QKD） system, imperfect equipment, especially the single-photon detector,can be eavesdropped on by a blinding attack. However, the original blinding attack may be discovered by directly detecting the current. In this paper, we propose a probabilistic blinding attack model, where Eve probabilistically applies a blinding attack without being caught by using only an existing intuitive countermeasure. More precisely, our countermeasure solves the problem of how to define the bound in the limitation of precision of current detection, and then we prove security of the practical system by considering the current parameter. Meanwhile, we discuss the bound of the quantum bit error rate（QBER） introduced by Eve, by which Eve can acquire information without the countermeasure.